2019
DOI: 10.1101/659490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recounting the FANTOM Cage Associated Transcriptome

Abstract: Long non-coding RNAs (lncRNAs) have emerged as key coordinators of biological and cellular processes. Characterizing lncRNA expression across cells and tissues is key to understanding their role in determining phenotypes including disease. We present here FC-R2, a comprehensive expression atlas across a broadly-defined human transcriptome, inclusive of over 100,000 coding and non-coding genes as described by the FANTOM CAGE-Associated Transcriptome (FANTOM-CAT) study. This atlas greatly extends the gene annota… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…First in this work, we demonstrated that, through analysis of qRT‐PCR, LINC01311 was downregulated in AB1‐42‐treated SH‐SY5Y cells. Previously, LINC01311 aberrant expressions in human tissues were only found in liver and prostate cancers 8,9 . This work is the first one to show that LINC01311 is also dysregulated in neurogenerative human‐lineage neurons, thus prompting the interest of exploring its expression in human patients with neurogenerative diseases.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…First in this work, we demonstrated that, through analysis of qRT‐PCR, LINC01311 was downregulated in AB1‐42‐treated SH‐SY5Y cells. Previously, LINC01311 aberrant expressions in human tissues were only found in liver and prostate cancers 8,9 . This work is the first one to show that LINC01311 is also dysregulated in neurogenerative human‐lineage neurons, thus prompting the interest of exploring its expression in human patients with neurogenerative diseases.…”
Section: Discussionmentioning
confidence: 79%
“…In recent decades, emerging evidence has demonstrated that lncRNAs may be aberrantly expressed in human brains, and may be important and functional regulators for the development and progression of neurodegenerative disorders, 5 including AD 6,7 . Among them, LINC01311 is a novel lncRNA which was recently identified during human genome‐wide screening to be aberrantly expressed in human liver and prostate cancers 8,9 . Yet, the functional role of LINC01311 in human diseases has never been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This feature facilitated generating the four quantifications included in recount3, ranging from smaller, more stringent annotations (RefSeq, O'Leary et al (2016)), to more inclusive annotations (GENCODE, Frankish et al (2019)), and to annotations focusing on 5' boundaries and non-coding RNAs (FANTOM-CAT, Hon et al (2017)). The advantage of diverse annotations is illustrated by the FC-R2 study (Imada et al, 2020), which quantified recount2's bigWigs using the FANTOM-CAT annotation, which includes a large number of non-coding RNAs (Hon et al, 2017). The study reported the tissue specificity of different classes of RNA: coding mRNA, divergent promoter lncRNA, intergenic promoter lncRNA, and enhancer lncRNA.…”
Section: Non-coding and Unannotated Transcriptionmentioning
confidence: 99%
“…Non-coding and unannotated transcription. Using recount3's FANTOM-CAT quantifications, we updated the previous analysis (Imada et al, 2020) to use the recount3 quantifications, including the additional runs present in GTEx v8. Briefly, this involving computing the counts per million (CPM) for the GTEx v8 data, then computing the entropy across the different GTEx tissues, and using the FANTOM-CAT annotation (Imada et al, 2020) we made Figure 4a.…”
Section: Analysesmentioning
confidence: 99%
“…The FANTOM5 project also used CAGE to annotate TSSs in mammalian and avian genomes (Andersson et al, 2014;Forrest et al, 2014;Imada et al, 2020). The FANTOM5 data release contained putative TSSs for human, mouse, chicken, rhesus monkey, and dog.…”
Section: Fantom5 Mammalian and Avian Cage Tssmentioning
confidence: 99%